EKSISTENSI PEREMPUAN PEKERJA RUMAHAN DALAM KONSTELASI RELASI GENDER - Triana Sofiani (UIN K.H. Abdurrahman Wahid Pekalongan, 2010)
Abstrac: The contribution given by the real of Ho`me Women Workers, though it seemed almost in the whole scope of life, but their presence does not count, either by families, communities, institutions and state support. This happens because they are women, which of course in the constellation of gender relations, any work undertaken by women's reproductive work considered the economic and of course it doesnâ€™t need to get respect like that done by men. As a result, the work done by home womenÂ workers work only as a shadow or work under the surface. So in the informal sector are not monitored and there are no statistics report on the state, even in the free area legal protection.